The Motorcycle Diaries Youth, Travel and Politics in Latin America - LIE, Nadia (Cinema and Youth Cultures, 2023)
The first monograph to examine Walter Salles' The Motorcycle Diaries, this book explains the significance of Salles' film with respect to the specific category of 'youth culture' as a historically and culturally situated concept. The Motorcycle Diaries looks at the film's engagement with 'emerging adulthood', the importance of travel as a source of self-discovery, and the film's impact on the iconicity of Che Guevara, the international emblem of a restless, rebellious youth. Combining insights from transnational film studies, tourism studies and affect theory, as well as drawing on extensive historical materials, this book provides not only a necessary addition to existing scholarship on this popular movie, but also an inspiring model for the analysis of film in relation to youth culture - a burgeoning field of interest in Latin American scholarship. It will interest any scholar in film studies, specifically transnational cinemas, global cinema, Latin American cinema, Latin American history, postcolonial studies, cultural studies, tourism studies and global politics.